Analisis Cemaran Klorin Pada Beras Dengan Metode Volumetri Studi Kasus : Kabupaten Bone Bolango - Muhammad Taupik; Andi Makkulawu; A. Mu’thi Andy Suryadi; Jafar La Kilo (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Rice is a staple food because it contains protein needed by the body is a source of energy. Rice that is white and shiny sometimes attracts people’s attention. Therefore, to increase buyers’ interest, many sellers add bleaching additives such as chlorine ( a chemical to kill germs) without reckoning the side effects that will be inflicted. This study examines the chlorine content in circulated rice in Bone Bolango Regency. This study used seven rice samples to be analyzed through color and precipitation tests. This research implements a mixed method in the form of qualitative as well as Iodometric and Argentometry titrations for quantitative. The results reveal that in the seven rice samples studied, there was no chlorine content due to the absence of discoloration and precipitate. It is supported by the Iodometric and Argentometric tests which show the results of chlorine levels are at 0%.